2003
DOI: 10.1213/01.ane.0000059742.62646.40
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-Induced Anesthesia in Mice Is Mediated by γ-Aminobutyric Acid-A and Excitatory Amino Acid Receptors

Abstract: We examined behaviorally the effects of GABAergic and glutamatergic drugs on propofol-induced anesthesia in mice. The results suggest that propofol anesthesia is mediated, at least in part, by both GABA(A) and excitatory amino acid receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…By contrast, propofol is considered to be less likely to produce anaesthetic effects through an NMDAR-dependent mechanism. This is because a large number of studies have shown that propofol anaesthetises via enhancing GABA-ergic transmission [18,19]. Therefore, propofol may be a more appropriate anaesthetic for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, propofol is considered to be less likely to produce anaesthetic effects through an NMDAR-dependent mechanism. This is because a large number of studies have shown that propofol anaesthetises via enhancing GABA-ergic transmission [18,19]. Therefore, propofol may be a more appropriate anaesthetic for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after drug injection, each animal was placed in a chamber (20 Â 28 Â 15 cm) with an electric heat pad, and the righting reflex was assessed every 2 minutes for a maximum of 2 hours. Anesthesia was evaluated using the following scoring system (Irifune et al, 2003): 0, normal righting reflex; 1, righting within 2 seconds; 2, righting latency 2-10 seconds; 3, no righting within 10 seconds. Anesthetic scores were determined every 2 minutes as the median of three trials.…”
Section: Methodsmentioning
confidence: 99%
“…Presumably because of the improvement in muscle coordination, PRO-treated mice also showed normalization of righting times. Despite the well-known ability of PRO to enhance GABA A R activity (Belelli et al, 1999;Jurd et al, 2003), causing anesthesia on higher-dose intraperitoneal injection (e.g., 140 mg/ kg; Irifune et al, 2003), the low doses of PRO used in this study did not appear to have anesthetic or sedative effects. Because a large reduction for GABA A R-mediated inhibitory transmission was also found in the tg271Q-300 mice (Becker et al, 2002) and mice carrying a point mutation in the ␤ 3 subunit of the GABA A R display a reduction in the loss of the righting reflex after PRO treatment (Jurd et al, 2003), a pleiotropic effect of subanesthetic PRO concentrations at both GABA A Rs and GlyRs cannot be excluded.…”
Section: Discussionmentioning
confidence: 65%